Pengaruh Social Media Marketing, Product Knowledge terhadap Keputusan Pembelian Ramen melalui Minat Sebagai Variabel Intervening - Shifa, Adelin Audya; Nurjanah, Siti (STREAMING, 2022)
This study aims to determine the effect of social media marketing and product knowledge on purchase decisions of mika ramen kari with purchase intention as an intervening variable. There are four variables in this study, namely social media marketing, product knowledge, purchase decisions and purchase intention. This study uses quantitative methods using purposive sampling technique which is part of non-probability sampling. The questionnaire was distributed using google form with a sample of 180 respondents who were people who knew and had consumed mika ramen kari. The tests used in this research are validity test, reliability test, classical assumption test, hypothesis test and path analysis test. The results showed that the variables of social media marketing and product knowledge had an effect on purchasing decisions and buying interest. But the buying interest variable as an intervening variable does not mediate between the independent variable and the dependent variable.